Interaction Between Commensal Bacteria, Immune Response and the Intestinal Barrier in Inflammatory Bowel Disease - Chen, Yongyan; Cui, Wenwen; Li, Xiao; Yang, Huan (Frontiers in Immunology, 2021)
In inflammatory bowel disease (IBD), intestinal mucosa cell and intestinal epithelial cell are severely damaged, and then their susceptibility to bacteria increases, so many commensal bacteria become pathogenic. The pathogenic commensal bacteria can stimulate a series of compensatory immune responses in the intestine. However, the immune response prevents the intestinal tract from restoring homeostasis, which in turn produces an indispensable inflammatory response. On the contrary, in IBD, the fierce inflammatory response contributes to the development of IBD. However, the effect of commensal bacteria on inflammation in IBD has not been clearly studied. Therefore, we further summarize the changes brought about by the changes of commensal bacteria to the inflammation of the intestines and their mutual influence. This article reviews the protective mechanism of commensal bacteria in healthy people and the mechanism of commensal bacteria and immune response to the destruction of the intestinal barrier when IBD occurs. The treatment and prevention of IBD are also briefly summarized.